On the Issue of Memory Politics in Kharkiv in 2010-2016 - Куценко, Денис (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
The article shows how memory politics of Kharkiv city authorities changed in 2010-2016, how this politics was affected by Euromaidan, war at the Eastern Ukraine, president elections in Ukraine in 2014. In the first part it is shown, how symbolic space of Kharkiv city space was ukrainized by authorities and local activists. Analysis of instructions and cultural programs passed by the City Council allows to make some conclusions about changes in cultural politics and way of national and local holidays celebrating in the second part of the article.